Suicidal behavior of mental health service users: Theories and research - Dragišić Labaš, Slađana M (Sociološki pregled, 2020)
This paper considers general and specific risk factors for suicidal behavior among vulnerable and marginalized mental health service users, employing specific sociological, psychological and psychiatric theories. We seek to explain the necessity of applying a multidimensional approach to this phenomenon and integrating knowledge from the three scientific fields. The paper emphasizes why it is essential to account not only for the individual but also for the social dimension of the problem. People with mental and psychosocial disabilities are more vulnerable concerning all risk factors that come from family and society. Stigma and discrimination, along with recognized social factors related to suicide risk in general population (economic crisis, inequality, migration, war, unemployment ...), are shown to further worsen their health and social status. Negative attitudes towards people with mental disabilities, especially those linking them with dangerousness, aggressiveness and unpredictability, significantly impede their taking part in society. With unequal opportunity, social exclusion and the loss of dignity, suicide seems to often present itself as a way out.